2022
DOI: 10.1002/anie.202212948
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalyst‐Enabled Regio‐ and Stereodivergent Synthesis of α‐Quaternary α‐Amino Acids via Asymmetric Allylic Alkylation of Aldimine Esters with Racemic Allylic Alcohols

Abstract: We describe cooperative bimetallic catalysis that enables regio-/stereodivergent asymmetric α-allylations of aldimine esters. By employing Et 3 B as the key activator, racemic allylic alcohols can be directly ionized to form Pd or Ir-π-allyl species in the presence of achiral Pd or chiral Ir complexes, respectively. The less or more substituted allylic termini of the metal-π-allyl species are amenable to nucleophilic attack by the chiral Cuazomethine ylide, the formation of which is simultaneously facilitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 112 publications
0
22
0
Order By: Relevance
“…Scheme 18 Asymmetric umpolung coupling of aldimine esters and allylic alcohols via cooperative bimetallic catalysis by Dang and Wang in 2022. 26 year, Wang et al also reported an unprecedented copper/ruthenium relay catalysed stereodivergent hydroalkylation of racemic allylic alcohols and racemic ketimine esters. 27 Merging the ruthenium-catalysed asymmetric borrowing-hydrogen reaction with a copper-catalysed asymmetric Michael addition reaction into a one-pot procedure provided a route to highly functionalized d-hydroxyesters bearing 1,4-nonadjacent stereocenters in good yields with excellent stereoselectivity under mild reaction conditions.…”
Section: Allylic/propargylic Substitution With Imine Derivativesmentioning
confidence: 99%
“…Scheme 18 Asymmetric umpolung coupling of aldimine esters and allylic alcohols via cooperative bimetallic catalysis by Dang and Wang in 2022. 26 year, Wang et al also reported an unprecedented copper/ruthenium relay catalysed stereodivergent hydroalkylation of racemic allylic alcohols and racemic ketimine esters. 27 Merging the ruthenium-catalysed asymmetric borrowing-hydrogen reaction with a copper-catalysed asymmetric Michael addition reaction into a one-pot procedure provided a route to highly functionalized d-hydroxyesters bearing 1,4-nonadjacent stereocenters in good yields with excellent stereoselectivity under mild reaction conditions.…”
Section: Allylic/propargylic Substitution With Imine Derivativesmentioning
confidence: 99%
“…However, there are no reports on metal-catalyzed asymmetric cascade annulations of the indoline-2-thiones. Herein, we describe the application of Bronsted base and Lewis acid cooperative activation [ 44 , 45 , 46 , 47 ] to the synthesis of spiro[indoline-3,4′-thiopyrano[2,3- b ]indole] derivatives via the Friedel–Crafts alkylation/cyclization tandem reactions of indoline-2-thiones and isatylidene malononitriles [ 48 , 49 , 50 , 51 ] ( Scheme 1 b).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous reports and control experiments, 10,18 a plausible mechanism was proposed in Scheme S2 (seeing ESI†). The decarboxylation of vinylethylene carbonate 2a under Pd(0) catalysis would generate π-allylpalladium complex F , which isomerizes to six-membered palladacycle intermediate G , 17 a ,17 b which was able to react with complexed azomethine ylide chiral species D to form linear α-quaternary trisubstituted allylic amino acid 3ba , PdL(0) complex, and CuL*.…”
mentioning
confidence: 99%
“…9 Zhang's and Wang's groups independently reported regioselective and enantioselective construction of linear α,α-disubstituted amino acids via asymmetric allylic alkylation of the amino acid-derived aldimine or ketimine esters by Pd/Cu synergistic catalysis under base conditions. 10 Despite these great improvements, their reported methods are limited to preparing chiral disubstituted allylic amino acid scaffolds with the E -configuration. Therefore, a general asymmetric catalytic methodology for the regio- and stereoselective construction of highly functionalized multisubstituted ( Z )-configurational allylic amino acids from simple and variable substrates remains an enormous challenge and will be particularly appealing.…”
mentioning
confidence: 99%